IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA FLIP BOOK BERTEMA LINGKUNGAN HIDUP UNTUK MENINGKATAN HASIL BELAJAR SISWA KELAS III SDIT MUHAMMADIYAH BIREUEN - Triana, Dinda; Rizki , Sari; Zuhra, Intan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low learning outcomes of third-grade students at SDIT Muhammadiyah Bireuen in the Natural and Social Sciences (IPAS) subject, particularly on the topic of the environment. The study aimed to determine the effect of implementing the Problem Based Learning (PBL) model assisted by an environmental-themed flipbook on improving the learning outcomes of third-grade students at SDIT Muhammadiyah Bireuen. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of all third-grade students of SDIT Muhammadiyah Bireuen in the 2025/2026 academic year, comprising two classes. The sample was selected using a saturated sampling technique, with Class IIIA serving as the experimental group and Class IIIB as the control group. The research instruments included pretest and posttest assessments, observation sheets, and documentation. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing through the Independent Samples t-test with the assistance of SPSS version 25. The findings revealed that the implementation of the Problem Based Learning model assisted by an environmental-themed flipbook had a positive effect on students' learning outcomes. This was evidenced by the higher mean posttest score achieved by the experimental group compared to the control group, as well as the hypothesis test results indicating a statistically significant difference at the 5% significance level. Therefore, it can be concluded that the implementation of the Problem Based Learning model assisted by an environmental-themed flipbook is effective in improving the learning outcomes of third-grade students at SDIT Muhammadiyah Bireuen.